Generation Z and The Sustainability of Indonesia's Local Culture - Ahmad Karno Djaba; Endang Sungkawati; Sonny Leksono (AMCA Journal of Community Development, 2025)
This research aims to describe the elements that cause Generation Z to be uninterested in pursuing local culture as cultural heritage and the role of stakeholders for Generation Z in the preservation and continuity of local culture in Indonesia. This research uses a qualitative descriptive research method with a case study approach. Primary data collection techniques include interviews, observations, documents, and focus group discussions. The informant selection technique was carried out through purposive sampling. Data validity uses source triangulation and data analysis techniques through data reduction, data display, and conclusion drawing/verification. The research results show that the reason Generation Z is not interested in studying local culture is because the manufacturing process is long and complicated, lazy and tedious work, and not economical. Stakeholders who play a role in increasing Generation Z's desire for local cultural sustainability consist of a) family, b) government, and c) community leaders. The role of stakeholders in sustaining local culture for Generation Z is mentoring and training SMEs to create and preserve local crafts, increasing competence, assistance with production materials, copyright protection for local craft products, and collaboration between agencies and institutions to support the younger generation in having enthusiasm. to want to learn and be skilled, publish literature related to guidelines or guides on how to preserve local crafts in hardcopy and e-book.